The State and Employers' Associations in British Columbia: 1900-1932 - Yarmie, Andrew (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2000)
Abstract Through a case study of British Columbia employers' associations this article examines the complexity of capital/state/labour relations during the early 20th century. To evaluate the sources of employers' strength and to determine the restrictions placed on their dominance, this study uses current theories of the state as a framework. They provide opportunities to examine British Columbia's governments as being either a "captive state," in a position of "relative autonomy," or "autonomous." No single theory explains the events of this period. In some sectors of the economy, employers were able to control state policy, but the contradictions created by the state's two primary objectives of capital accumulation and legitimation ensured that it would take steps to retain its autonomy in order to maintain capitalist class institutions.